People at Risk of Influenza Pandemics: The Evolution of Perception and Behavior. - Jianhua Xu; Zongchao Peng (PLoS ONE)
Influenza pandemics can severely impact human health and society. Understanding public perception and behavior toward influenza pandemics is important for minimizing the effects of such events. Public perception and behavior are expected to change over the course of an influenza pandemic, but this idea has received little attention in previous studies. Our study aimed to understand the dynamics of public perception and behavior over the course of the 2009 H1N1 influenza pandemic. Three consecutive cross-sectional surveys were administered among Beijing residents with random-digit dialing techniques in March 2008 and August and November 2009. Effective samples of 507, 508 and 1006 respondents were interviewed in each of the three surveys, respectively. The mean scores of risk perception were low to moderate across the three surveys. The perceived risk of infection of self was significantly lower than that of the community, revealing an optimistic bias. Longitudinally, the perceived risk of contracting H1N1 increased, whereas the perceived risk of being unable to obtain medicine and medical care once influenza permeated the community first increased and then decreased. Responsive actions toward influenza varied. Most respondents took actions that required little extra effort, such as ventilating rooms; these actions did not change over time. Comparatively, a smaller number of respondents took actions for coping with influenza, such as vaccination; however, these actions were taken by an increasing number of respondents over time. The association between risk perception and behavior was unstable. Positive, insignificant, and negative associations were obtained in the three surveys. In conclusion, the evolving patterns of risk perception and responsive behavior over the course of an influenza pandemic are sensitive to how risk and behavior are defined and scoped.